2009
DOI: 10.1002/cncr.24546
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of O6‐methylguanine‐DNA methyltransferase silencing in patients with recurrent glioblastoma multiforme who undergo surgery and carmustine wafer implantation

Abstract: BACKGROUND: O6‐methylguanine‐DNA methyltransferase (MGMT) is a key enzyme in the DNA repair process after alkylating agent action. Epigenetic silencing of the MGMT gene by promoter methylation has been associated with longer survival in patients with newly diagnosed glioblastoma multiforme (GBM) who receive alkylating agents. In this study, the authors evaluated the prognostic value of different biomarkers in recurrent GBM and analyzed the changes in MGMT status between primary tumors and recurrent tumors. MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 41 publications
1
44
1
Order By: Relevance
“…A small randomized trial from Finland in glioblastoma or anaplastic astrocytoma patients aged > 65 showed a median survival of 171 days after resection versus 85 days after biopsy (p=0.035). 25 This study has been criticized because of small patient numbers (n=30 enrolled, 13 versus 10 patients per arm evaluable) and major KPS imbalances between arms.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
See 1 more Smart Citation
“…A small randomized trial from Finland in glioblastoma or anaplastic astrocytoma patients aged > 65 showed a median survival of 171 days after resection versus 85 days after biopsy (p=0.035). 25 This study has been criticized because of small patient numbers (n=30 enrolled, 13 versus 10 patients per arm evaluable) and major KPS imbalances between arms.…”
Section: Glioblastoma (Who Grade Iv)mentioning
confidence: 99%
“…[15][16][17][18][19] The demonstration of promoter methylation of the MGMT gene assessed by methylation-specific PCR or pyrosequencing of bisulfite-modified DNA is associated with superior outcome in anaplastic glioma patients treated with radiotherapy or alkylating agent chemotherapy 19,20 and with specific benefit from temozolomide (TMZ) in glioblastoma patients. [21][22][23][24] Retesting the MGMT status at recurrence is not necessary since the methylation status remains stable, at least in glioblastoma, 25,26 …”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…13 All primers and probes have been published elsewhere. 21 The differences in amounts of input genomic DNA were normalized by the collagen type II, alpha 1 gene (COL2A1).…”
Section: Methylightmentioning
confidence: 99%
“…Pyrosequencing is a sequence-by-synthesis method that is the only method analyzing methylation levels at each CpG separately (for review and comparison of techniques, see Weller et al 2 and Preusser 3 ). Currently, among these alternative techniques, only pyrosequencing 11,12 and MethyLight 13 have been shown to have predictive value for GBM patients. Furthermore, a realtime quantitative MS-PCR approach, proposed by MDxHealth (formerly Oncomethylome Sciences), is being used in several international clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary evidence suggests that survival may be improved in patients with mgmt promoter hypermethylation at recurrence 39 . Survival in those cases is reported to be in the range of 25-35 weeks 40 , but may be adversely affected by postoperative complications such as bone marrow suppression, infection, and poor wound healing 41,42 .…”
Section: Repeat Surgerymentioning
confidence: 99%